Multi-angular scatterometer measurements for various stages of rice growth - Lim, Ka-Sing; Koo, Voon Chet; Ewe, Hong-Tat (EMW Publishing, 2008)
This paper presents comprehensive measurements of radar backscatter from rice crops using a ground-based 6 GHz C-band scatterometer system. The measurements were conducted over an entire season from the early vegetative stage of the plants to the ripening stage with full polarization combinations of HH, VV, HV and VH at the incident angle range from 0 degrees. to 60 degrees.. The objective of this paper is to access the use of the ground-based scatterometer data for the investigation of temporal variation of different incident angle in the rice growth monitoring application. A further study on the angular response for different rice growth stages was also performed in order to have a better understanding of the backscattering behavior of the rice crops and therefore, monitoring of rice crops growth using operational scatterometer system.